Nosema ceranae prevalence in high and low honey producing colonies of African-derived honey bees (Apis mellifera) in Brazil - Kadri, Samir M. [UNESP]; Fulton, James C.; Prouty, Cody; Epperson, Kiley J.; Orsi, Ricardo O. [UNESP]; Ellis, James D. (Taylor & Francis, 2025)
African-derived honey bees (AHBs) show documented resistance to many of the pest/pathogen species known to impact managed honey bee colonies. In this study, we attempted to correlate pathogen levels with low (LHP) and high (HHP) honey production tendencies in managed AHB colonies in Brazil. LHP colonies were 15.81× more likely to be infected with Nosema ceranae than were HHP colonies. The prevalence rates for other pathogens were low and not correlated with honey production.